2021
DOI: 10.1111/jai.14262
|View full text |Cite
|
Sign up to set email alerts
|

Length–weight relationship of six endemic fish species in the Qinghai‐Tibet Plateau, China

Abstract: Length-weight relationships (LWRs) of fish are applied to elucidate relationship between total length or standard length and body weight (Duvan Gomez-Vanega & López-Uriarte, 2021;Munilkumar et al., 2021;Zhang et al., 2018). LWRs are useful in fishery science and management provided they are obtained in combination with other essential parameters required for stock assessment (Danielle, 2017). Generally, LWRs can be also used to compare the condition of a species from different habitats when all studies involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
5
1
Order By: Relevance
“…In this study, the estimated b value ranged from 2.557 to 3.228 that remained within the expected range (2.5 to 3.5) (Froese, 2006). There were some deviations of the b value simulated in this study for partial endemic species when compared with other studies (Akhtar & Fiaz Khan, 2018; Chen et al, 2017; Sui et al, 2015; Yang et al, 2021). The differences in the b values may be due to several factors such as methodology and effort of fishing, type of habitat, seasonality, geographic region, health, species, sex, diet, etc.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…In this study, the estimated b value ranged from 2.557 to 3.228 that remained within the expected range (2.5 to 3.5) (Froese, 2006). There were some deviations of the b value simulated in this study for partial endemic species when compared with other studies (Akhtar & Fiaz Khan, 2018; Chen et al, 2017; Sui et al, 2015; Yang et al, 2021). The differences in the b values may be due to several factors such as methodology and effort of fishing, type of habitat, seasonality, geographic region, health, species, sex, diet, etc.…”
Section: Discussioncontrasting
confidence: 60%
“…Length–weight relationships (LWRs) are important in fishery management and applied extensively to fishery research in the QTP (Lin et al, 2017; Xie et al, 2018; Yang et al, 2021). However, most studies of endemic fishes focused on these river basins such as Yarlung Tsangpo River, the Lancang River, the Nujiang River, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the presently reported study are concordant with the expected range. It has been shown that when b is greater than three, fish grow faster in weight than in length (Islam et al 2017;Yang et al 2021). In addition, a b value lower than 3.0 signifies that fish expend more energy on axial growth than to accumulate mass, which could help them seek food and avoid predators (Yang et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that when b is greater than three, fish grow faster in weight than in length (Islam et al 2017;Yang et al 2021). In addition, a b value lower than 3.0 signifies that fish expend more energy on axial growth than to accumulate mass, which could help them seek food and avoid predators (Yang et al 2021). The calculations performed in this study indicate that, in Iskandaria kuschakewitschi, Paracobitis longicauda, and Triplophysa daryoae, parameter b was lower than 3.0, which may be due to cold water, severe environment, low availability of food resources, the large abundance of predators and food competitors, and other unpredictable reasons (Le Cren 1951;Rypel and Richter 2008;Wang et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Length-weight relationships (LWRs) and length-length relationships (LLRs) are significant tools in fisheries management for the proper understanding of growth pattern and condition of fish species from different habitats (Jennings et al 2001;Wang et al 2016;Yang et al 2022). The LWRs are also used for the interconversion of length to weight and weight to length in order to determine growth at specific length (Bolarinwa and Popoola 2013).…”
Section: Introductionmentioning
confidence: 99%